Perception and Implementation of Integrated Talent Management System (ITMS): A Comparative Study of the Tunisian and Palestinian Public Sectors – Insights from IBM Institute for Business Value - Abusahloub, Iyad Ahmed; Elfidha, Chokri (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to assess the perception and implementation of the Integrated Talent Management System (ITMS) using IBM Institute standards. It conducted a comparative analysis between the Palestinian and Tunisian public sectors between 2016 and 2018, focusing on the implementation level, perception of ITMS. Additionally, it examined the relationship between ITMS implementation and perception, the organizational culture based on Hofstede's dimensions, and the mediating role of organizational culture on this relationship.A descriptive-analytical approach was employed, using a structured questionnaire based on IBM Institute standards. The instrument was enhanced with sections measuring ITMS perception and perception, and organizational culture based on Hofstede’s five cultural dimensions. The study sample comprised upper and middle-level managers, including 384 participants from Tunisia and 248 from Palestine. Statistical analyses were conducted using SPSS and AMOS. The study revealed significant differences between the Tunisian (66.78%, moderate) and Palestinian (47.99%, low) public sectors in ITMS implementation. Perception of ITMS were relatively close, with Tunisia scoring 74.19% and Palestine 82.28% (both high levels). Organizational culture strength was moderate in Tunisia (55.53%) but low in Palestine (43.36%). The ITMS dimensions positively influenced ITMS perception in both sectors, with stronger relationships in Palestine. Organizational culture partially mediated the relationship between ITMS implementation and perception in both sectors. The Tunisian public sector requires enhanced implementation of ITMS dimensions, particularly talent communication and empowerment. The Palestinian public sector needs to address all ITMS dimensions comprehensively while prioritizing talent strategy development and talent acquisition/retention.
Keywords: IBM standards; Public sector; Integrated Talent Management System ITMS; Organizational culture; Palestine; Tunisia